2009
DOI: 10.1002/sia.3047
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of saccharides by X‐ray photoelectron spectroscopy

Abstract: A series of saccharides, including several monohydrates and one amorphous phase, has been investigated by XPS, providing the first database of survey and high-resolution spectra for this class of compounds. Known stoichiometries and XPS-determined elemental compositions agree well. XPS has sufficient precision for distinguishing the stoichiometries of mono-, di-, and polysaccharides. The C 1s chemical shifts of the acetal and alcohol groups are similar for all samples, albeit with slight binding energy increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 20 publications
6
86
2
1
Order By: Relevance
“…An additional species attributed to carboxyls (CO 2 R) originating probably from irradiation-induced oxidations or dehydroxlations was included at 289.6 eV. [16] Owing to their low overall prevalence, thiol-specific components (C-S) are not separable from C-C and/or C-O moieties. This notion is supported by a sulfur amount of 2 atom% as estimated from survey spectra (cf Table S1, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…An additional species attributed to carboxyls (CO 2 R) originating probably from irradiation-induced oxidations or dehydroxlations was included at 289.6 eV. [16] Owing to their low overall prevalence, thiol-specific components (C-S) are not separable from C-C and/or C-O moieties. This notion is supported by a sulfur amount of 2 atom% as estimated from survey spectra (cf Table S1, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…High resolution core level spectra were measured with a pass energy of 20 eV, 0.1 eV steps, and 300 ms dwell time per data point. 9,17 Analysis of the data was carried out with CasaXPS software. 20 A linear background and GL(30) lineshape were used in all curve-fitting 9,17 and samples were referenced to adventitious hydrocarbon contamination at 285 eV except for those containing 5-sulfosalicylic acid, which were referenced to aromatic carbon at 284.8 eV.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar manner to NMR, shifts in XPS occur with changes in the chemical environment, in this case as a result of the differing amounts of energy (binding energy, E B ) required to emit an electron from an atomic core level. 9,16,17 To test the ability of XPS to distinguish between a salt and co-crystal of an API, solution crystallisation and milling were employed to form a theophylline salt 18 and co-crystal, 6 with 5-sulfosalicylic acid dihydrate (2-hydroxy-5-sulfobenzoic acid) and oxalic acid (ethanedioic acid, Fig. 1) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…XPS has been earlier used to detect differences in the amounts of calcium and phosphorous as a sign of mineralisation on the culture substrate before and after osteoblast culture (Mustafa et al, 2002). XPS is also suitable for recognition of different www.ecmjournal.org E Kaivosoja et al Spectroscopy in the analysis of footprints monosaccharides, disaccharides, and polysaccharide (Stevens and Schroeder, 2009). However, in our study, with a much more complex ECM and EPS as the study objects, only minor differences were observed between MSC-and S. aureus-culture samples so that a reliable separation of them was impossible.…”
Section: Discussionmentioning
confidence: 99%